(untitled) (Research, Society and Development, 2020)
This study aimed to examine the lives of fishermen communities, found, and also discussed appropriate empowerment models for fishermen communities in Sub-District Belawan, Medan. Data collection through survey methods was done by distributing questionnaires to 100 fishermen communities. An in-depth interview method was also done to 4 informants consisting of the local chief and the fishermen communities. Through the results of descriptive analysis, it was found that the partnership – based empowerment model was an appropriate model with the situation and conditions of the fishermen communities in Sub-District Belawan, Medan. This partnership-based empowerment consisted of facilities assets, training, governance, developing access facilities of fisheries business, and strengthening fishing skills. However, some other aspects needed to be renewed in the fishermen communities, such as built the concepts of understanding the education meaning for fishermen communities and made approaches in mass, individual, and group to the communities. This was done to increase communities’ motivation to participate in existing empowerment activities. The results of this paper were formulated in the form of communities and appropriate technology for the fishermen communities of Belawan.